Benefits from Social Capital and Entrepreneurship Enhancement - Mbu Daniel Tambi; Mofow Neville Zoatsa (LPPM of NAROTAMA UNIVERSITY)
This study employed Multiple Correspondence Analyses to construct a social capital index and verified its relationship with entrepreneurship enhancement through Probit model correcting for endogeneity using the Cameroon household consumption survey in Stata. The results indicate that benefits from social capital is strongly correlated with entrepreneurship enhancement, while result by gender of household head, shows that entrepreneurship promotion is stronger among the female as compare to the male counterparts. The same applies for the rural than urban businessmen. We suggest that support policies by donors should be granted to useful associations, and that the government should invest in social capital either directly or indirectly by creating an environment friendly to the emergence of local associations.